Petrifyin’: Canonical Counter-Discourse in Two Caribbean Women’s Medusa Poems - Phillip Zapkin (Humanities, 2022)
This essay utilizes Helen Tiffin’s idea of canonical counter-discourse to read the Medusa poems of Shara McCallum and Dorothea Smartt, two female Caribbean poets. Essentially, canonical counter-discourse involves authors rewriting works or giving voice to peripheral/silenced characters from the literary canon to challenge inequalities upheld by power structures such as imperialism and patriarchy. McCallum’s and Smartt’s poems represent Medusa to reflect their own concerns as women of color from Jamaica and Barbados, respectively. McCallum’s “Madwoman as Rasta Medusa” aligns the titular character from her book Madwoman with Medusa to express Madwoman’s righteous anger at the “wanton” and “gravalicious” ways of a Babylon addressed in second person. Smartt’s series of Medusa poems from Connecting Medium explore the pain of hair and skin treatments Black women endure to try and meet Euro-centric beauty standards, as well as the struggles of immigrants, particularly people of color. Both poets claim Medusa as kindred, empowering Medusa as a figure with agency—which she is denied in the Greco-Roman sources—and simultaneously legitimizing both Caribbean literature and the poets’ feminist and post-colonial protests by linking them to the cultural capital of the classics.